İstanbul'daki Bizans saraylari = Byzantine palaces in Istanbul - Denker, Asuman (İstanbul Arkeoloji Müzeleri, 2011)
Catalogue published on the occasion of the exhibition "Byzantine Palaces in Istanbul" opened on 21st June 2010 by the Istanbul Archaeological Museums with the support of the Vehbi Koç Foundation. The exhibition was designed to accompany the symposium titled "The Byzantine Court: Source of Power and Culture" and it presented the finds from salvage excavations. Naturally, the Great Palace occupies a great place in the exhibition and its catalogue. Furthermore, selected items from the palaces of Bukoleon, Antigonos, Blacherna, Myrelaion, Rhegion, Mangana, Botaneiates, and Hebdomon are presented. Although the items are not of great spectacle, they provide us with invaluable information regarding the decoration of the now lost buildings. The catalogue is further enhanced with 3-D reconstruction drawings by T. Oner